Hysterotomy- Indications and Associated Complications: An Indian Teaching Hospital Experience - Siwatch, S; Sehgal, E; Goyal, LD (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: To analyze the incidence, indications, period of gestation and associated morbidity and mortality of hysterotomy in a tertiary care hospital in India. Methods: Ten year inpatient records of abortions and hysterotomies at a tertiary care government teaching hospital in North India were reviewed and analyzed. Results: The incidence of hysterotomy at our institute was 1.1% of all abortions. Fifty two hysterotomies were performed. Majority of the women were multigravidas and in the second trimester of pregnancy. Haemorrhage due to placenta previa was the commonest indication for surgery. Failed induction for medical termination of pregnancy (MTP) and previous caesarean were the other common causes. Hysterotomy was associated with considerable morbidity. Conclusions: Abortion in any trimester may be associated with need for surgical intervention which may be associated with serious morbidity. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11136 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 17-20